Socio‐demographic vulnerability to heatwave impacts in Brisbane, Australia: a time series analysis - Ghasem (Sam); Yuming Guo; Lyle Turner; Xin Qi; Peter Aitken; Shilu Tong (Elsevier, 2014)
Abstract Objective: Examining the association between socioeconomic disadvantage and heat‐related emergency department (ED) visits during heatwave periods in Brisbane, 2000-2008. Methods: Data from 10 public EDs were analysed using a generalised additive model for disease categories, age groups and gender. Results: Cumulative relative risks (RR) for non‐external causes other than cardiovascular and respiratory diseases were 1.11 and 1.05 in most and least disadvantaged areas, respectively. The pattern persisted on lags 0-2. Elevated risks were observed for all age groups above 15 years in all areas. However, with RRs of 1.19-1.28, the 65-74 years age group in more disadvantaged areas stood out, compared with RR=1.08 in less disadvantaged areas. This pattern was observed on lag 0 but did not persist. The RRs for male presentations were 1.10 and 1.04 in most and less disadvantaged areas; for females, RR was 1.04 in less disadvantaged areas. This pattern persisted across lags 0-2. Conclusions: Heat‐related ED visits increased during heatwaves. However, due to overlapping confidence intervals, variations across socioeconomic areas should be interpreted cautiously. Implications: ED data may be utilised for monitoring heat‐related health impacts, particularly on the first day of heatwaves, to facilitate prompt interventions and targeted resource allocation.